How do we incorporate patient views into the design of healthcare services for older people: a discussion paper - Paul R. Brocklehurst; Gerald McKenna; Martin Schimmel; Anastassia Kossioni; Katarina Jerković-Ćosić; Martina Hayes; Cristiane da Mata; Frauke Müller (BMC, 2018)
Abstract Background Across the European Union costs for the treatment of oral disease is expected to rise to €93 Billion by 2020 and be higher than those for stroke and dementia combined. A significant proportion of these costs will relate to the provision of care for older people. Dental caries severity and experience is now a major public health issue in older people and periodontal disease disproportionately affects older adults. Poor oral health impacts on older people's quality of life, their self-esteem, general health and diet. Oral health care service provision for older people is often unavailable or poor, as is the standard of knowledge amongst formal and informal carers. The aim of this discussion paper is to explore some of the approaches that could be taken to improve the level of co-production in the design of healthcare services for older people. Main text People's emotional and practical response to challenges in health and well-being and the responsiveness of systems to their needs is crucial to improve the quality of service provision. This is a particularly important aspect of care for older people as felt, expressed and normative needs may be fundamentally different and vary as they become increasingly dependent. Co-production shifts the design process away from the traditional 'top-down' medical model, where needs assessments are undertaken by someone external to a community and strategies are devised that encourage these communities to become passive recipients of services. Instead, an inductive paradigm of partnership working and shared leadership is actively encouraged to set priorities and ultimately helps improve the translational gap between research, health policy and health-service provision. Discussion The four methodological approaches discussed in this paper (Priority Setting Partnerships, Discrete Choice Experiments, Core Outcome Sets and Experience Based Co-Design) represent an approach that seeks to better engage with older people and ensure an inductive, co-produced process to the research and design of healthcare services of the future. These methods facilitate partnerships between researchers, healthcare professionals and patients to produce more responsive and appropriate public services for older people.